1977
DOI: 10.1507/endocrj1954.24.149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulpiride on serum growth hormone and prolactin concentrations following L-DOPA administration in man.

Abstract: SynopsisThe effect of chronic administration of sulpiride on serum human growth hormone (hGH), prolactin and thyroid stimulating hormone (TSH) was examined in 6 normal subjects. Sulpiride was given orally at a dose of 300 mg (t. i. d.) for 30 days. Sulpiride raised serum prolactin levels in all subjects examined.In addition, sulpiride suppressed hGH release induced by L-dopa, although the basal hGH level was not changed.Sulpiride treatment appeared to antagonize partially the inhibitory effect of L-dopa on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Although many studies have documented SVinduced PRL release in patients under various conditions of treatment (23)(24)(25) and the pharmacokinetics of SV has also been studied (26,27,28), these two aspects of the problem have not been investigated simultaneously in the same subjects. Moreover, the fate of PRL after SV administration had neither been followed for: more than 4 hours nor were the two most commonly used dosages in current therapeutics compared in the same subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have documented SVinduced PRL release in patients under various conditions of treatment (23)(24)(25) and the pharmacokinetics of SV has also been studied (26,27,28), these two aspects of the problem have not been investigated simultaneously in the same subjects. Moreover, the fate of PRL after SV administration had neither been followed for: more than 4 hours nor were the two most commonly used dosages in current therapeutics compared in the same subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The action of sulpiride on prolactin secre¬ tion has been assumed to be exerted at the hypo¬ thalamus, possibly by acting against the dopaminergic mechanism (Mori et al 1977;MacLeod & Robyn 1977), although the possibility that its effect is exerted directly at the pituitary level cannot be excluded (Debeljuk et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Further¬ more, Holland et al (1977) could not find any evidence for a possible role of prolactin in stimulat¬ ing aldosterone. Thus, they concluded that prolac¬ tin was not an important osmoregulatory hormone in man.It has been postulated that sulpiride could be used in the dynamic functional exploration of pituitary prolactin release in man (Mancini et al 1976;Mori et al 1977). The present stydy was undertaken to examine the question of whether serum osmotic changes might affect pituitary pro¬ lactin secretion in response to sulpiride administra¬ tion in man.…”
mentioning
confidence: 99%